2019
DOI: 10.3389/fphar.2019.00784
|View full text |Cite
|
Sign up to set email alerts
|

3-Chloroplumbagin Induces Cell Death in Breast Cancer Cells Through MAPK-Mediated Mcl-1 Inhibition

Abstract: Resistance acquired toward anti-cancer agents is a significant drawback in breast cancer therapy. A key factor contributing to drug resistance is apoptosis suppression associated with the upregulation of anti-apoptotic Bcl-2 family proteins. Specifically, the anti-apoptotic Mcl-1 protein has been shown to play a significant role in drug resistance, making it an important therapeutic target. The present study aimed at determining the antiproliferative activity of 3-chloroplumbagin (ChPL), a naphthoquinone deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Using BCL2 inhibitors for these metastatic cases improved cancer cell apoptosis in a preclinical model of breast cancer [ 7 , 8 ]. Genes that are involved in this biological process are dipeptidyl peptidase ( DPP ) family genes, extracellular-signal-regulated kinase ( ERK ), GATA-binding protein 3 ( GATA3 ), signal transducer and activator of transcription 3 ( STAT3 ), phosphatidylinositol 3-kinase ( PI3K ), and NOTCH [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using BCL2 inhibitors for these metastatic cases improved cancer cell apoptosis in a preclinical model of breast cancer [ 7 , 8 ]. Genes that are involved in this biological process are dipeptidyl peptidase ( DPP ) family genes, extracellular-signal-regulated kinase ( ERK ), GATA-binding protein 3 ( GATA3 ), signal transducer and activator of transcription 3 ( STAT3 ), phosphatidylinositol 3-kinase ( PI3K ), and NOTCH [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The healing properties of these plants arise from the ability to produce large amounts of phenolic compounds with strong biological activity (Gaascht et al 2013 ). Extracts from carnivorous plant tissues were proven to have antibacterial (Krolicka et al 2008 ; Makowski et al 2020 ), antioxidative (Królicka et al 2009 ; Makowski et al 2020 ), antifungal (Padhye et al 2010 ), and anticancer properties (Kawiak et al 2019 ). Moreover, previous phytochemical studies showed that the species most abundant in phenolic derivatives in the family Droseraceae is D. muscipula (Gaascht et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…As shown, the extracts from carnivorous plants from the family, Droseraceae, have strong antioxidant [5], antibacterial [1,6] and antifungal [7] properties. Recently, Kawiak et al [8] showed that they also have anticancer properties. Due to the growing resistance for antibiotics of some human-pathogenic microbes, and the increasing demand for new drugs in cancer therapy, plant material with strong biological activity are in great demand.…”
Section: Introductionmentioning
confidence: 99%